Do South African international cricket pace bowlers have similar bowling volume and injury risk associates compared to other elite fast bowlers? - Christie, C. J.; McEwan, K.; Munro, C. E.; King, G. A.; Le Roux, A.; Olivier, B.; Jackson, B.; Manjra, S.; MacMillan, C.; Pote, L. (International Journal of Sports Science & Coaching, 2023)
Background Although many cricket-playing nations have conducted research on bowling volume (BV) and injury risk, this relationship amongst international South African pace bowlers is yet to be investigated. Environmental, socio-economic and training strategy differences warrant similar research in a South African context. The purpose of this preliminary study was to establish whether South African pace bowlers have similar BV and injury associates compared to other elite fast bowlers. Methods This study was a prospective, observational, cohort study that monitored match and training BV and injuries amongst pace bowlers playing for the South African national team between April 2017 and April 2019. A sample of convenience that included 14 bowlers was selected. Bowling volume was quantified as the number of deliveries bowled during training and competition. Acute-, chronic- and acute:chronic BV ratios were independently modelled as association variables. Results There were 39 injuries with the most being to the lumbar spine (25.64%). Moderate-to-low and a moderate-to-high acute:chronic bowling load ratios were associated with a lower risk of injury. Chronic bowling load was associated with injury (z = 2.82, p = 0.01). A low acute workload, low chronic workload, moderate-high chronic workload and moderate-low acute:chronic ratio were also associated with an increased risk of injury. Conclusion These findings confirm that there appears to be a dose-response effect between training BV and the likelihood of an injury occurring with a moderate-to-low and a moderate-to-high BV ratio being optimal. Considering the small sample size, the findings should be interpreted with caution.